Testing the unitary theory of language lateralization using functional transcranial Doppler sonography in adults - Woodhead, Z; Bradshaw, A; Wilson, A; Thompson, P; Bishop, D (Royal Society, 2019)
Hemispheric dominance for language can vary from task to task, but it is unclear if this reflects error of measurement or independent lateralization of different language systems. We used functional transcranial Doppler sonography to assess language lateralization within the middle cerebral artery territory in 37 adults (seven left-handers) on six tasks, each given on two occasions. Tasks taxed different aspects of language function. A pre-registered structural equation analysis was used to compare models of means and covariances. For most people, a single lateralized factor explained most of the covariance between tasks. A minority, however, showed dissociation of asymmetry, giving a second factor. This was mostly derived from a receptive task, which was highly reliable but not lateralized. The results suggest that variation in the strength of language lateralization reflects true individual differences and not just error of measurement. The inclusion of several tasks in a laterality battery makes it easier to detect cases of atypical asymmetry.